Antisipasi kejadian sindrom metabolik melalui skrining kesehatan metode point of care testing (POCT) - Abbas, Mutmainnah; Saptenno, Lidya B. E.; Husein, Anggun Lestary; Mus, Rosdiana; Tanihatu, Genevieva Esmeraldine; Latuheru, Grace (Jurnal PADE: Pengabdian & Edukasi, 2025)
Metabolic syndrome is a complex metabolic disorder caused by obesity, insulin resistance, dyslipidemia, and hypertension. The increase in the prevalence of metabolic syndrome in Maluku Province is very significant, starting from an early age with various risk factors, one of which is diet. Therefore, early detection of potential disease development in the future is necessary through basic medical diagnostic tests, namely Point of Care Testing. (POCT). The method used involves 3 stages: preparation, implementation, and evaluation of activities, and it involves 62 participants. The activity took place in Soya Village, Ambon City, after it was found that there was a low level of public awareness about regularly undergoing health check-ups at the community health center and a tendency to consume foods high in sugar, salt, and fat daily. The results of this activity revealed that 47 (75.8%) people have high systolic blood pressure and 38 (61.3%) people have high diastolic blood pressure. Blood glucose levels showed that 58 (93.5%) people had normal levels. Uric acid levels were normal in 41 (66.1%) people, and cholesterol levels were high in 40 (65.5%) people. This refers to the risk factors for the development of cardiovascular disease.Keywords: Metabolic syndrome, Blood pressure, Blood glucose, Cholesterol, Uric acid, POCT